2009
DOI: 10.1177/0192623309345691
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Calcitonin Gene-Related Peptide Receptor during Ozone Inhalation Contributes to Airway Epithelial Injury and Repair

Abstract: The authors investigated the importance of the neuropeptide, calcitonin gene-related peptide (CGRP), in epithelial injury, repair, and neutrophil emigration after ozone exposure. Wistar rats were administered either a CGRP-receptor antagonist ) or saline and exposed to 8 hours of 1-ppm ozone or filtered air with an 8-hour postexposure period. Immediately after exposure, ethidium homodimer was instilled into lungs as a marker of necrotic airway epithelial cells. After fixation, airway dissected lung lobes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
1
4
1
Order By: Relevance
“…However, examination by electron microscopy showed clear alterations in the epithelial structure with enlarged intercellular space and disrupted junctions between adjacent cells in the tracheas of O 3 exposed newborn mice. This is in contrast to previous studies in adult rats where epithelial damage tended to occur more in distal airways than in the proximal airways after 8 h of exposure to 1000 ppb O 3 (Oslund et al, 2009). This apparent difference may be due to differences in the age of animals and duration of O 3 exposure.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…However, examination by electron microscopy showed clear alterations in the epithelial structure with enlarged intercellular space and disrupted junctions between adjacent cells in the tracheas of O 3 exposed newborn mice. This is in contrast to previous studies in adult rats where epithelial damage tended to occur more in distal airways than in the proximal airways after 8 h of exposure to 1000 ppb O 3 (Oslund et al, 2009). This apparent difference may be due to differences in the age of animals and duration of O 3 exposure.…”
Section: Discussioncontrasting
confidence: 98%
“…In our newborn mouse model, the results of rt-qPCR showed that CGRP mRNA expression was increased significantly (1.92 ± 0.16-fold) but transiently at 6 h post-O 3 exposure. CGRP may play a role in epithelial injury and repair after O 3 exposure as recently suggested (Oslund et al, 2009). Our results also demonstrate increased expression of the neuropeptide GRP at 24 h post-O 3 exposure.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, a protective role of neuropeptitergic system has also been documented. VIP influences many respiratory functions, protects bronchial epithelial cells against damage, produces airway relaxation, inhibits SMC proliferation and reduces inflammation [ 74 ]. CGRP regulates inflammation and promotes epithelial repair [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ex vivo treatment with CGRP increased SPC‐ir granule size and number, suggesting an effect on AT2 cell quantity and function. While CGRP has previously been shown to induce epithelial cell proliferation in cell lines, changes in SPC granule number and size have rarely been reported in PCLS (Dakhama et al., 2004; Fu et al., 2010; Kawanami et al., 2009; Li, Cohen, et al., 2020; Oslund et al., 2009). The change in SPC immunoreactivity in the tissue may indicate a change in tissue alveolar cell coverage because a greater number of observed granules and AT2 cells will result in less space for alveolar type 1 (AT1) projections.…”
Section: Discussionmentioning
confidence: 99%